Pricing decision model for new and remanufactured short-life cycle products with time-dependent demand - Shu San Gan; I. Nyoman Pujawan; Suparno; Basuki Widodo (Operations Research Perspectives, 2015)
In this study we develop a model that optimizes the price for new and remanufactured short life-cycle products where demands are time-dependent and price sensitive. While there has been very few published works that attempt to model remanufacturing decisions for products with short life cycle, we believe that there are many situations where remanufacturing short life cycle products is rewarding economically as well as environmentally. The system that we model consists of a retailer, a manufacturer, and a collector of used product from the end customers. Two different scenarios are evaluated for the system. The first is the independent situation where each party attempts to maximize his/her own total profit and the second is the joint profit model where we optimize the combined total profit for all three members of the supply chain. Manufacturer acts as the Stackelberg leader in the independently optimized scenario, while in the other the intermediate prices are determined by coordinated pricing policy. The results suggest that (i) reducing the price of new products during the decline phase does not give better profit for the whole system, (ii) the total profit obtained from optimizing each player is lower than the total profit of the integrated model, and (iii) speed of change in demand influences the robustness of the prices as well as the total profit gained.
Keywords: 330; Short life cycle product; Remanufacturing; Closed loop supply chain; Pricing; Optimization